Body diode reliability investigation of SiC power MOSFETs. (September 2016) - Fayyaz, A.; Romano, G.; Castellazzi, A.
Abstract: A special feature of vertical power MOSFETs, in general, is the inbuilt body diode which could eliminate the need of having to use additional anti-parallel diodes for current freewheeling in industrial inverter applications: this, clearly, subject to their demonstration of an acceptable level of reliability. Recent improvements in Silicon Carbide (SiC) power MOSFET device manufacturing technology has resulted in their wider commercial availability with different voltage and current ratings and from various manufacturers. Hence, it is essential to perform characterisation of its intrinsic body diode. This paper presents the reliability assessment of body diodes of latest generation discrete SiC power MOSFETs within a 3-phase 2-level DC-to-AC inverter representing realistic operating conditions for power electronic applications. Highlights: Body diode reliability investigation of SiC power MOSFET is presented in this paper. Devices were stressed within a 3-phase 2-level inverter. For comparison, devices of similar ratings from two different manufacturers were tested. Body diode forward voltage drop (Vf ) and drain leakage current (ILEAK ) were monitored at regular intervals. Possible physical mechanisms responsible for electrical parameter degradation of Vf and ILEAK are also briefly discussed.